ANALISIS MAKNA ADAT TOKUWELA DI DESA SANGOWO KABUPATEN PULAU MOROTAI DAN IMPILIKASINYA BAGI PENGEMBANGAN SASTRA DAERAH - Rianti Sibua; Sulami Sibua (Universitas Khairun, 2022)
This study was conducted with the aim of describing the meaning of tokuwela adat in Sangowo Village, and to describe the implications for regional literature in Sangowo Village. The method used in this research is descriptive qualitative by using several data collection techniques in the study, namely observation, interviews and documentation. Based on data analysis, it is concluded that the meaning of tokuwela custom is a type of dance, namely the dance of the spirit of togetherness. Which is carried out during the wedding procession, the evening procession for young people's entertainment, the procession to enter a new house and entertain guests. in the wedding procession this dance has a meaning as building a generous household and conveying their joy, then the evening procession of entertainment for young people this dance has a meaning as only to enliven their village and they enjoy the entertainment, then the procession enters a new house which has meaning as gratitude, gratitude for what they get, and the last is the procession of welcoming guests which has the meaning as showing a sense of appreciation even though the person is not yet known by the local community. And for the implications for regional literature, the culture of the people of Morotai Island, especially in Sangowo Village, is a reflection of the sincerity of the soul and the spirit of being grateful for the gift of God Almighty to the land of its people.